Analisis Faktor Yang Mempengaruhi Respon Pengobatan TB Paru Lini Pertama Di RSUD Tugurejo Semarang - Nadya Rachma Fachriah; Afiana Rohmani; Setyoko Setyoko (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
One of the infectious diseases that still poses a threat to the world is tuberculosis (TB). When a person is diagnosed with tuberculosis, anti-tuberculosis drugs (ATD) should be administered as soon as possible as part of their treatment. Treatment for tuberculosis may be impacted by a number of factors, including age, gender, comorbidities, and nutritional status. The purpose of this study is to ascertain how age, gender, nutritional status, and comorbidities relate to the response of patients receiving first-line pulmonary tuberculosis treatment at Tugurejo Hospital Semarang using Anti Tuberculosis Drugs category one. This kind of cross-sectional, analytical observational research is being conducted. Response to first-line pulmonary tuberculosis treatment was the dependent variable, and independent variables included age, gender, nutritional status, and comorbidities. 50 patients in all were selected as samples from Tugurejo Regional Public Hospital's medical files. Statistical analysis used the chi-square test for bivariate and the logistic regression test for multivariate. The analysis's findings demonstrated a significant relationship (p-value 0.001) between nutritional status and treatment response, as well as a significant relationship (p value 0.005) between comorbidities and treatment response. However, there was no significant correlation found between the age and gender variables (p values of 0.617 and 0.425). The results of the logistic regression showed that comorbidities and nutritional status had significant results with the OR value of comorbidities (OR 13,622, 95% CI 2.207-84.075, p= 0.005) and nutritional status (OR 7.208, 95% CI 1.783-29.138, P=0.006). There is a noteworthy correlation between the response to first-line pulmonary tuberculosis treatment and nutritional status and comorbidities at Tugurejo Hospital Semarang. At Tugurejo Hospital Semarang, there is a noteworthy correlation between the response to first-line pulmonary tuberculosis treatment and nutritional status and comorbidities.